2020
DOI: 10.1108/apjml-10-2019-0576
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediating role of social interactivity between customer engagement and brand loyalty

Abstract: PurposeThis study aims at identifying and examining the mediating role of customer engagement behavior and social interactivity onbrand loyalty.Design/methodology/approachA correlational study design was adopted in this study to collect data (online survey) from 400 online participants active on Facebook pages.FindingsEmpirical results reveal that there is a significant and positive impact of social interactivity on consumer engagement behavior and brand loyalty.Research limitations/implicationsThe findings wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 73 publications
1
34
0
6
Order By: Relevance
“…Previous studies found significant and positive relationships between virtual interactivity and brand involvement (e.g. Hollebeek et al 2014;Ting et al, 2020). Thus, H3c: Virtual interactivity positively influences brand involvement.…”
Section: Information Quality Rewards and Virtual Interactivity Effects On Brand Involvementmentioning
confidence: 80%
“…Previous studies found significant and positive relationships between virtual interactivity and brand involvement (e.g. Hollebeek et al 2014;Ting et al, 2020). Thus, H3c: Virtual interactivity positively influences brand involvement.…”
Section: Information Quality Rewards and Virtual Interactivity Effects On Brand Involvementmentioning
confidence: 80%
“…In the era of digital industry, customer engagement has a strategic role in achieving business success as an important transcendent relational idea. Besides, it is shown as a tool to develop and improve relationships with customers (Ting, Abbasi, & Ahmed, 2020). Customer engagement has a significant place and plays an important role in understanding the consequences associated with customers, such as consequences related to loyalty (Graffigna & Gambetti, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Customer engagement is a manifestation of customer behavior towards a particular company, brand or product that involves the company's efforts to empower and motivate customer contributions (Ting et al, 2020). Marketing Science Institute (2015) describes customer engagement as a manifestation of customer behavior towards brands outside of purchasing activities resulting from individual's motivation such as word of mouth, recommendations, interaction between customers, blogging, writing reviews and other similar activities.…”
Section: Introductionmentioning
confidence: 99%
“…(Bilro & Loureiro, 2020;Ting et al, 2020).On the contrary, concerning the experience of product consumption, consumers commit repeated journeys with the company and their social networks. Consumer engagement consists of the consumer satisfaction level and consumer emotional connectedness level; thus, consumer engagement may have three dimensions(Monferrer et al, 2019;Parihar et al, 2019;Venkatesan, 2017).…”
mentioning
confidence: 99%